Intravitreal Methotrexate in Treatment of Noninfectious Uveitic Macular Edema - Yasmena Abdulhadi; Suliman Masuod; Nada Elsaeid; Majdoleen Ramadan (AlQalam Journal of Medical and Applied Sciences, 2021)
Objectives: To assess the outcomes of the intravitreal administration of methotrexate in noninfectious uveitic macular edema. Methods. Prospective interventional case series of patients with noninfectious uveitic macular edema. Twenty-seven eyes of 27 patients were enrolled, intravitreal injections of methotrexate at a dose of 400 mg in 0.1 mL. The primary outcome measure was visual acuity. Secondary outcome measures included control of intraocular inflammation and cystoid macular edema, time to relapse, development of adverse events, and levels of systemic corticosteroid and immunosuppressive therapy. Results. Methotrexate proved effective in controlling intraocular inflammation and improving vision in 25 of 27 eyes (92%). The side effect profile was good, with no reported serious ocular adverse events and only one patient having an intraocular pressure of 25 mmHg. Of the 27 eyes that responded to treatment, 2 relapsed (7%), but 23 (92%) entered an extended period of remission. The two eyes that relapsed were reinjected and all responded to treatment. Of the 27 patients on systemic therapy at the start of the study, 19 (70%) were able to significantly reduce this following intravitreal methotrexate injection. Conclusion. In patients with uveitis and uveitic cystoid macular edema, intravitreal MTX can effectively improve visual acuity and reduce cystoid macular edema and, in some patients, allows the reduction of immunosuppressive therapy. However, some patients relapse at 3 to 4 months, but a large proportion (92%) enter an extended period of remission of up to 6 months.